THE IMPACT OF ECONOMIC FREEDOM ON INBOUND TOURISM IN MENA REGION FROM 2000 TO 2018: A PANEL DATA ANALYSIS USING R SOFTWARE. (El-Wahat Journal for Research and Studies, 2023)
Abstract:The Purpose Of This Paper Is To Investigate The Relation Between The Freedom Of Economy And The Performance Of Inbound Tourism In MENA Region. Using R Software, A Panel Data Analysis Was Performed Over The 18 Mena Region Countries From 2000 To 2018. The Results Shows That Judicial And Monetary Policies Have Both An Impact On Inbound Tourism, In Fact, International Tourism Performance Rises When Property Rights Are Better Secured And The Legal System Is More Autonomous. In Addition, Stable Money And Higher Level Of Freedom To Own Foreign Currency Accounts Impacts Positively Inbound Tourism. The Study Also Found That The Inbound Tourism Performance In North-African Countries Is Related To The Freedom To Trade Internationally, While In The Middle-East Region, Government Size Is Reported To Have An Impact On Incoming Tourism.Keywords: Inbound Tourism, Economic Freedom, Panel Data Regression,